Is Intravenous Urography Required When Ultrasonography and KUB Evidence a Ureteroscopy Plan? - Aghamir, Seyed Mohammad Kazem; Modaresi, Seyed Saeed; Salavati, Alborz; Aloosh, Mehdi; Meysami, Ali Pasha (Urology Journal, 2012)
PURPOSE: To determine whether pre-ureteroscopic stone extraction (USE) evaluation by intravenous urography (IVU) can change the clinical decision made on the basis of a plain X-ray of the kidneys, ureters, and bladder (KUB) plus an ultrasonography in the case of ureteral calculi. MATERIALS AND METHODS: From October 2005 to November 2007, 139 USE candidates were selected based on ultrasonography and KUB, and were randomly divided into two groups. Each group was assessed by an expert urologist to decide about the treatment plans. Thereafter, all the patients underwent an IVU pre-operatively and were evaluated for the second time by the other urologist considering IVU. Presence of a hydronephrotic kidney on the ultrasonography, existence of a density in the probable tract of the ureter on KUB, and previous episodes of renal colic were considered as inclusion criteria. Exclusion criteria were non-opaque stones on KUB, hypersensitivity to contrast media, and serum creatinine > 1.5 mg/dL. RESULTS: On the basis of ultrasonography and KUB assessment, all of the patients were identified candidate for USE. According to secondary IVU-based planning, of 139 patients, 127 (91.3%) required USE, 10 (7.1%) ureteroscopy, and 2 (1.4%) non-operative treatment. About 8.7% of treatment plans was changed by IVU, which was not statistically significant (P = .35). Positive predictive value of ultrasonography plus KUB to diagnose a ureteral stone which needed USE was 92.8% while IVU is the gold standard (95% confidence interval: 92.38 to 93.22). CONCLUSION: Intravenous urography is not useful enough to be performed routinely before entire USEs.